Socio-demographic and Epidemiological Characterisation of Leprosy in the Population of Pará, Amazon, from 2016 to 2020 - Marcela Raissa Asevedo Dergan; Nelson Veiga Gonçalves; Luiz Fábio Magno Falcão; Dayara de Nazaré Rosa de Carvalho; Thiago Augusto Ferreira dos Anjos; Vera Regina da Cunha Menezes Palácios (Archives of Current Research International, 2023)
Objective: To describe the sociodemographic and epidemiological characteristics of the population with leprosy in the State of Pará from 2016 to 2020. Methodology: Cross-sectional ecological study, based on data from the Disease Information and Notification System (SINAN). The study was conductedin 144 municipalities in Pará, Amazon. The data were organised and distributed by 12 integration Regions. Results and Discussion: In the analysed data, a total of 11,687 cases of leprosy were verified in Pará from 2016 to 2020. Sociodemographic data showed a predominance in the male population, in the brown race, and in those with low education, this study demonstrated that leprosy is prevalent in vulnerable populations with low socioeconomic status, highlighting social inequalities. Conclusion: Monitoring epidemiological and operational indicators of leprosy is essential for evaluating programs and planning public health policies to contribute to epidemiological surveillance.